2012
DOI: 10.2147/opth.s37252
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up of ranibizumab combined with photodynamic therapy for polypoidal choroidal vasculopathy

Abstract: PurposeWe evaluated the 2-year efficacy of combined intravitreal ranibizumab (IVR) treatment and photodynamic therapy (PDT) for treatment-naïve polypoidal choroidal vasculopathy (PCV).Patients and methodsTwenty-two eyes of 22 Japanese patients with treatment-naïve PCV were prospectively recruited. All eyes had angiographic features of PCV according to indocyanine green angiography. The initial combination treatment regimen included a session of PDT with IVR. A total of three consecutive IVR treatments were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The visual gain diminishes after 6 months to 1 year and the final visual acuity at 2 years is not statistically different from the baseline. 141143 It is possible that if PDT is applied days after the anti-VEGF injection (half-life of the drug), the collegial benefit of the combined treatment may be limited.…”
Section: Medical Managementmentioning
confidence: 99%
“…The visual gain diminishes after 6 months to 1 year and the final visual acuity at 2 years is not statistically different from the baseline. 141143 It is possible that if PDT is applied days after the anti-VEGF injection (half-life of the drug), the collegial benefit of the combined treatment may be limited.…”
Section: Medical Managementmentioning
confidence: 99%
“…Two studies reported similar results, i.e. that visual acuity significantly improved during the first year of treatment, but that the benefit decreased during the second year [32,33]. A recent study compared 2-year visual outcomes between PDT alone and combination therapy [24].…”
Section: Discussionmentioning
confidence: 99%